2016
DOI: 10.4166/kjg.2016.67.5.257
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mucosa-associated Lymphoid Tissue Lymphoma Metachronously Involving Esophagus and Stomach

Abstract: Mucosa-associated lymphoid tissue (MALT) lymphoma is found in various organs as extranodal B cell lymphoma. The gastro-intestinal tract is the most commonly involved extranodal site in MALT lymphoma. However, primary esophageal MALT lymphoma is very rare. In addition, few cases with metachronous gastric involvement have been reported. A 55-year-old man was diagnosed with MALT lymphoma by surveillance esop hagogastroduodenoscopy. A 5 cm esophageal submucosal tumor-like lesion was incidentally revealed by screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Primary esophageal lymphoma is a rare tumor, and there only 25 case studies of MALT lymphoma in the esophagus have been reported to date (4, 5, 6-28). In the previously reported cases, esophageal MALT lymphoma was treated with surgical resection (7-12), rituximab and/or chemotherapy (12-19, 27, 28), radiotherapy (8, 12, 20-22, 28), endoscopic resection (20-26), and Hp eradication therapy (4, 5, 7, 8, 12, 13, 27); however, a standard treatment remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Primary esophageal lymphoma is a rare tumor, and there only 25 case studies of MALT lymphoma in the esophagus have been reported to date (4, 5, 6-28). In the previously reported cases, esophageal MALT lymphoma was treated with surgical resection (7-12), rituximab and/or chemotherapy (12-19, 27, 28), radiotherapy (8, 12, 20-22, 28), endoscopic resection (20-26), and Hp eradication therapy (4, 5, 7, 8, 12, 13, 27); however, a standard treatment remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Ten of the 22 reported cases with esophageal MALT lymphoma were diagnosed using a conventional biopsy during esophagogastroduodenoscopy as well. Five cases were diagnosed after surgical resection of the esophageal tumor ( 8 , 9 , 19 , 23 , 25 ). Other procedures include endoscopic mucosal resection (n=3) ( 7 , 14 , 15 ), endoscopic ultrasound-guided fine needle aspiration (n=2) ( 13 , 16 ), a stacked forceps biopsy (n=1) ( 22 ), and endoscopic submucosal dissection (n=1) ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, rituximab-containing chemotherapy regimens are administered for advanced-stage MALT lymphoma. Of note, in one patient, recurrence was detected in the stomach and lung 21 months after resection of localized esophageal MALT lymphoma ( 23 ). Therefore, gastroenterologists should be alert for the emergence of lymphoma involvement in the lung and stomach when monitoring disease relapse or progression in patients with esophageal MALT lymphoma.…”
Section: Discussionmentioning
confidence: 99%